2017
DOI: 10.1242/jcs.202036
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse reveals that osteoclasts can move across the bone surface while resorbing

Abstract: Bone erosion both demands that the osteoclast resorbs bone matrix and moves over the bone surface. It is widely accepted that these two activities alternate, because they are considered mutually exclusive since resorption is believed to involve an immobilizing seal to the bone surface. However, clear real-time observations are still lacking. Herein, we used specific markers and time-lapse to monitor live the spatiotemporal generation of resorption events by osteoclasts cultured on bone slices. In accordance wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 36 publications
(118 reference statements)
5
79
0
Order By: Relevance
“…Because the SZ is a barrier that limits the diffusion of acidic and proteolytic molecules released in the resorption lacunae (11)(12)(13)(14), increased adhesion would likely enhance the efficiency of containment and favor bone resorption (72). From these results, we propose that modification of several parameters of the SZ (i.e., increased size, adhesion, and degradative activity) contribute to the enhanced osteolytic activity and to the modifications of the topography of resorption pits on infection (12,36,73). Pharmacological destabilization of the SZ would reduce the impact of HIV-1 on bone degradation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Because the SZ is a barrier that limits the diffusion of acidic and proteolytic molecules released in the resorption lacunae (11)(12)(13)(14), increased adhesion would likely enhance the efficiency of containment and favor bone resorption (72). From these results, we propose that modification of several parameters of the SZ (i.e., increased size, adhesion, and degradative activity) contribute to the enhanced osteolytic activity and to the modifications of the topography of resorption pits on infection (12,36,73). Pharmacological destabilization of the SZ would reduce the impact of HIV-1 on bone degradation.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, we examined OC attachment/detachment, a critical factor for bone degradation (12), given that OC resorption partly proceeds through a succession of migratory phases alternating with bone resorption stationary phases (12,36). When infected, OC were more resistant to detachment induced by Accutase treatment than noninfected counterparts (Fig.…”
Section: Hiv-1 Infection Enhances Oc Precursor Migration and Oc Bonementioning
confidence: 99%
“…Osteoclasts change their cell shapes and exhibit the following states: motile resorbing osteoclasts [ 25 , 26 ], static resorbing osteoclasts, and motile non-resorbing osteoclasts [ 27 ]. When filamentous (F)-actin in osteoclasts cultured on mineralized matrices such as bone slices is stained with rhodamine-labeled phalloidin, ring-like structures of F-actin dots (therefore called actin rings) are observed in osteoclasts under fluorescent microscopy (Fig.…”
Section: Osteoclastsmentioning
confidence: 99%
“…Two phases of mature osteoclasts were observed using intravital multiphoton microscopy: static resorbing osteoclasts and motile non-resorbing osteoclasts [ 27 ]. However, it has recently been reported that osteoclasts move laterally on the bone surface and generate long trench without disassembling and reconstructing podosomes [ 25 , 26 ]. Thus, osteoclasts resorb bone under either two states such as pit or trench resorption modes (hereafter, resorption pits and trenches are simply called resorption cavities unless, otherwise, distinguished).…”
Section: Podosomesmentioning
confidence: 99%
“…Based on IVI, mature osteoclasts can be identified as two types: “static and bone‐resorbing” ones and “moving and non‐resorbing” ones . The two functional types are regarded as mutually exclusive, since resorption should involve an immobilizing seal to the bone surface according to previous view .…”
Section: Imaging Of Cellsmentioning
confidence: 99%